Exploring Self-existence through RajutKejut Craftivism: A case study in Penjaringan Forest, Jakarta - Sari Wulandari; Guntur Guntur; Martinus Dwi Marianto (IJCAS (International Journal of Creative and Arts Studies), 2020)
RajutKejut is a knitting community in Jakarta, Indonesia, that has been doing yarnbombing activities since 2014. In 2019, Jakarta Arts Council invited RajutKejut to collaborate with Kampung Air Baja residents in Penjaringan, North Jakarta, in a program called Young Curator Class: Titik Temu Gembira. The program combines forces between RajutKejut and urban village residents to explore life from a different perspective, specifically through art activism. This program’s spirit helps residents have joyful independent lives with dignity through art that encourages life’s passion. The RajutKejut Community shares its knowledge with residents on making necklaces from threads for their dance costumes. This research discusses how RajutKejut brings forward the passion of life through art activism. This research uses Alyce McGovern’s Craftivism method, which dissects craftivism in personal, community, and political aspects. It shows the relation of art to the residents, how art can influence and raise an individual’s potential. The community aspect shows the relation of art and the residents and how art can restore the spirit of togetherness and cooperation. On the political aspect, the art facilitates statements of empowerment from the residents. Through RajutKejut craftivism, the residents have the social capital to help them catch their breath for a while, stop their routines for a moment, and allow them to feel their existence as human beings who have expressions and feelings. Eksplorasi Eksistensi Diri melalui Kraftivisme RajutKejut: Studi Kasus di Hutan Penjaringan, Jakarta ABSTRAK RajutKejut adalah komunitas merajut di Jakarta, Indonesia yang telah melakukan kegiatan ‘bom-benang’ sejak tahun 2014. Pada tahun 2019, Dewan Kesenian Jakarta mengundang RajutKejut untuk berkolaborasi dengan warga Kampung Air Baja di Penjaringan, Jakarta Utara, dalam program Kelas Kurator Muda: Titik Temu Gembira. Program tersebut menggabungkan potensi komunitas RajutKejut dan warga kampung kota untuk mengeksplorasi kehidupan melalui perspektif yang berbeda, khususnya lewat aktivisme seni. Semangat program ini adalah membantu warga untuk memiliki kehidupan mandiri yang menyenangkan dan bermartabat, melalui seni yang mendorong gairah hidup. Komunitas RajutKejut berbagi pengetahuan kepada warga kampung kota, cara membuat kalung dari benang untuk kostum tari mereka. Penelitian ini membahas bagaimana RajutKejut mendorong gairah hidup melalui aktivisme seni. Penelitian ini menggunakan metode Craftivism Alyce McGovern, yang membedah craftivism dalam aspek personal, komunitas, dan politik. Penelitian menunjukkan relasi seni dengan warga kampung, bagaimana seni dapat mempengaruhi dan meningkatkan potensi individu. Dalam aspek komunitas, menunjukkan bagaimana seni berelasi dengan masyarakat dapat mengembalikan semangat kebersamaan dan kerjasama. Pada aspek politik, kesenian memfasilitasi pernyataan pemberdayaan dari warga kampung. Melalui kraftivisme RajutKejut, warga kampung memiliki modal sosial untuk membantu mereka mengatur napas sejenak, menghentikan rutinitas sejenak, dan memberi mereka kesempatan untuk merasakan keberadaannya sebagai manusia yang memiliki ekspresi dan perasaan.